A case of right ureteral stricture due to endometriosis in the pouch of Douglas - Takamura, C (Hinyokika kiyo. Acta urologica Japonica, 1989)
A case of right ureteral stricture due to endometriosis in the pouch of Douglas was presented. A 46-year-old housewife was referred to our clinic with asymptomatic macroscopic hematuria on August 22, 1985. Intravenous pyelography (IVP) and abdominal computed tomographic scanning revealed right hydronephrosis and retrograde pyelography showed that ureteral stenosis existed at the lower portion of the right ureter. Right stenotic ureter was removed in 5 cm and ureterovesiconeostomy with psoas hitch method was performed following hysterectomy, left adenexotomy, right salpingectomy on November 28, 1985. Pathological specimen of the ureter revealed that endometriosis existed around the ureteral mucosa. Medication with Danazol was started from the third operative day. Two months later, IVP revealed decreasing right hydronephrosis and she was quite healthy without complaints